From Lexington to Trenton. Some reflections on the element of water and it’s influence on military operations during the firts years of American War of Independence - Daszyńska, Jolanta A. (Armia kontra natura, 2020)
The battle of Lexington, 1775 started the American War of Independence. The Continental Army was raised by the Second Continental Congress on June 14, 1775 and two days after it fought in the first battle, known as the battle of Bunker Hill (June 17, 1775). George Washington was appointed as the Commander-in-Chief. He did not took part in it, staying already at Philadelphia.The British Pyrrhic victory caused the break in the fights till the Spring of 1776. In March because of a strong flury the British troops could not to attack, and as a result they left Boston on March 17. This day is celebrated as an Evacuation Day.While General Washington, with the American Army, was blockading the British garison in Boston, the other troops led the attack to invade Canada. They attacked from two maine rivers: The St. Lawrence River and St. Charles River. But the wide and ice covered rivers caused the big problem with transportation of soldiers. This time a snowstorm stopped the American attack, and they withdrew from Canada.The disastrous defeat of the Americans in the battle of Long Island on August 27, 1776 was the first battle after the Proclamation of Independence which led to the loss of New York and retreat to the Delaware River. Heavy rain was a non-attack factor.Among the presented battles, some of them were victories, but some were the defeats of the American soldiers. The nature and the elements of cold, frost, rains, snowstorms, icy roads and ice-covered rivers were not the ally for attacking troops. But sometimes, such an extreme weather conditions led to success, as it was during the battle of Trenton, after Washington’s famous crossing the Delaware River. The image on it is the best known battle picture in the world.